Passive Smoking as a Significant Risk Factor of Cervical Dysplasia: A Novel Findings in Single Center Study in Denpasar, Bali, Indonesia - Pradnyana, I Wayan Agus Surya; Mirani Ulfa Yusrika; I Gusti Bagus Mulia Agung Pradnyaandara; I Gde Sastra Winata (HM Publisher, 2024)
Background: Colposcopy is a diagnostic procedure evaluating the cervix following an abnormal screening test. It aims to identify and treat cervical cancer precursors. Risk stratification at the end of colposcopy helps differentiate those who can return to regular screening from those needing more frequent screening or surveillance. The study examined the characteristics and risk factors of patients undergoing colposcopy for cervical dysplasia in Denpasar, Bali, Indonesia. Methods: This was a cross-sectional study of women who underwent colposcopy at BaliMed Hospital, Denpasar, Bali, Indonesia, from January 2021-December 2022. Data were derived from medical records. The gynecology oncologist performed a colposcopy examination with a biopsy sample, which was later checked by the pathologist. Bivariate and multivariate analyses were used to identify the risk factors associated with cervical dysplasia. Results: 142 patients underwent colposcopy with a mean age of 37.28+10.1 years. Seventy-eight patients (54.9%) had a low-grade cervical lesion, and 9 (6.3%) had a high-grade cervical lesion. After adjusting the employment status and education level, factors associated with cervical dysplasia were age at first intercourse <20 years (aOR [adjusted odd ratio] 2.44, 95% CI [1.04-5.69]) and history of smoking, either actively or passively (aOR 8.91, 95% CI [3.52-22.54]). From the biopsy result, patients with abnormal cervical lesions were associated with evidence of CIN (aOR 9.03, 95% CI [2.49-32.77]). Conclusion: Early age first sexual intercourse and history of smoking have been identified as significant risk factors for cervical dysplasia. Additionally, passive smoking has been shown to increase the risk. This research provides a foundational reference for future studies in this area.